Toxicidade de inseticidas sobre abelhas sem ferrão - Araújo, Whalamys Lourenço de (2019)
Stingless bees are important pollinators and bioindicators of environmental quality; they also have socioeconomic importance. However, too much use of pesticides has contributed to their disappearance. The goal of this work is to evaluate the toxicity of insecticides used in melon trees and citrus cultivation on stingless bee species Jandaíra (Melipona subnitida), Uruçú (Melipona scutelaris) and Iraí (Nannotrigona testaceicornis). The tests were conducted at the Entomology Laboratory in the Center for Agricultural Sciences of the Federal University of Paraíba. The insecticides tested were the Neonicotinoid [Tiametoxam (T1) and Imidacloprido (T2)], Pyrethroid [Deltamethrin (T3) and Bifentrin (T6)], Organophosphate [Chlorpyrifos (T4)] and Biological [Bacillus thuringiensis (T5)] groups. The control treatment (T0) consisted of a water-based solution. In the Jandaíra test, the dosages used were the medians recommended by the manufacturers for melon trees. T0: Water; T1: 0.4 grams of the commercial product (g p. C.); T2: 0.3 g p. c.; T3: 0.03 milliliter of commercial product (ml p. C.); T4: 0.1 ml p.c.; T5: 0.33 ml p. c.; and T6: 0.1 ml p. c.; and with the Uruçú species recommended for citrus: T0: Water; T1: 0.02 g p. c; T2: 0.01 g p. c; T3: 0.03 ml p. c.; T4: 0.1 ml p.c.; T5: 0.33 ml p. c.; and T6: 0.02 ml p.c. The trials were arranged in a completely randomized design with 7 treatments, 10 replications containing 10 insects each. The bees were subjected to the topical application of 0.02 μl syrup of each treatment on the abdomen, with the aid of a syringe, and then confined in plastic pots (50 ml) sealed with perforated ventilation lids, kept under ambient conditions where honey and water were offered. For the trials with Iraí species, the neonicotinoid insecticide Tiametoxam (T1) and the organophosphate Clorpirifós (T2) were tested at the recommended dosages for citrus: T1: 0.02 g p. c and T2: 0.1 ml p. c., respectively. The experiments were arranged in a completely randomized design with 3 treatments, 10 replications containing 10 insects each, and two independent forms of contamination. ± 20 μL of spray mist was applied directly to the bees on each repetition. For surface contamination, the same content was applied via nebulization to plastic pots without the bees, which were put to dry, and later received the bees. The assays were kept at ambient Temperature and Relative Humidity, ± 27 ° C and ± 70%, respectively, where the bees were fed with honey and water. Behavioral observations, mortality rate accounting were done up to 96 hours. The data were submitted to survival analysis using GraphPad Prism (v.5 for Mac). Median survival time with a 95% confidence interval and xiii significant differences between groups were calculated using Kaplan – Meier and LogRank test, with a significance level of p <0.05. All chemical insecticides evaluated caused high mortality to stingless bees Jandaíra (M. subnitida) and Uruçú (M. scutelaris), except the biological insecticide. The neonicotinoid insecticide Tiametoxam caused high mortality to Iraí bee (N. testaceicornis), regardless of the form of exposure, while the organophosphate insecticide Clorpirifós caused a higher mortality rate when exposed via direct misting of the bees.